A generally minimalist strategy of constructing biomineralized high-efficiency personalized nanovaccine combined with immune checkpoint blockade for cancer immunotherapy. (October 2022) - Zhang, Sijia; Feng, Yuanji; Meng, Meng; Li, Zhen; Li, Huixin; Lin, Lin; Xu, Caina; Chen, Jie; Hao, Kai; Tang, Zhaohui; Tian, Huayu; Chen, Xuesi
Abstract: As a representative of tumor immunotherapy, tumor vaccine can inhibit tumor growth by activating tumor-specific immune response, which has the advantages of relatively low toxicity and high efficiency, and has attracted much attention in recent years. However, there are still difficulties in how to effectively deliver tumor vaccines in vivo and make them work efficiently. It is a relatively mature method to load tumor specific antigens with suitable carriers to produce tumor vaccines. Here, a generally minimalist construction method of tumor nanovaccine was developed. A high-efficiency tumor nanovaccine (NV) was prepared in one step by a biomineralization-like method, which contained ovalbumin (OVA, model antigen), unmethylated cytosine-phosphate-guanine (CpG, adjuvant) and Mn-NP (carrier and adjuvant). NV not only showed good tumor preventive effect, but also could successfully inhibited tumor development and metastasis when combined with anti-PD-L1, and induced long-term immune memory effect. However, the method of screening tumor specific antigen to construct nanovaccine is cumbersome and tumors are heterogeneous. Therefore, surgically resected tumor tissue is the best source of antigens for preparing tumor vaccines. Next, based on the strong loading ability of the carrier, we designed a personalized tumor nanovaccine (PNV) using the supernatant of tumor abrasive fluid (STAF) as antigen based on the generally minimalist tumor nanovaccine construction strategy. PNV combined with anti-PD-L1 could successfully inhibit post-surgical tumor recurrence and induce strong and durable immune memory effects. This study presents a novel, general, and minimalist strategy to construct high-efficiency personalized nanovaccine, which has a wide range of potential applications in the field of tumor treatment.